Development and prevalence of castration-resistant prostate cancer subtypes - Vellky, Jordan E. (Neoplasia, 2020)
BACKGROUND: Castration-resistant prostate cancer (CRPC) occurs when prostate cancer (CaP) progresses under therapy-induced castrate conditions. Several mechanisms have been proposed to explain this acquired resistance, many of which are driven by androgen receptor (AR). Recent findings, however, sub-classified CRPC by downregulation/absence of AR in certain subtypes that consequently do not respond to anti-androgen therapies. To highlight the significance of CRPC sub-classification, we reviewed the development and treatment of CRPC, AR downregulation in CRPC, and summarized recent reports on the prevalence of CRPC subtypes. METHODS: Using a medline-based literature search, we reviewed mechanisms of CRPC development, current treatment schemes, and assessed the prevalence of AR low/negative subtypes of CRPC. Additionally, we performed immunohistochemical staining on human CRPC specimens to quantify AR expression across CRPC subtypes. RESULTS: In the majority of cases, CRPC continues to rely on AR signaling, which can be augmented in castrate-conditions through a variety of mechanisms. However, recently low/negative AR expression patterns were identified in a significant proportion of patient samples from a multitude of independent studies. In these AR low/negative cases, we postulated that AR protein may be downregulated by (1) promoter methylation, (2) transcriptional regulation, (3) post-transcriptional regulation by microRNA or RNA-binding-proteins, or (4) post-translational ubiquitination-mediated degradation. CONCLUSIONS: Here, we discussed mechanisms of CRPC development and summarized the overall prevalence of CRPC subtypes; interestingly, AR low/negative CRPC represented a considerable proportion of diagnoses. Because these subtypes cannot be effectively treated with AR-targeted therapeutics, a better understanding of AR low/negative subtypes could lead to better treatment strategies and increased survival.